Analisis Peramalan untuk Persediaan Bahan Baku Penunjang Menggunakan Metode Forecasting pada PT. B - Hadi, Nur Ikhsan; Septiari, Renny; Soemanto, Soemanto (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
PT. B faces challenges in managing its raw material inventory due to fluctuations indemand and supply uncertainty, which can lead to excess or shortages. Thisnegatively impacts operational costs, customer service, and production continuity.Therefore, systematic and accurate inventory management is essential to reducewaste and the risk of supply chain disruptions. Forecasting methods such as movingaverages and exponential smoothing are used to predict raw material needs based onhistorical data and demand patterns. This study analyzes the application of theseforecasting methods at PT. B to find a more effective and efficient inventory controlsolution. Based on the selected forecast, the estimated demand for the upcomingperiod is estimated to be around 180,000 pcs of Ambri cigarette products. The resultsare expected to improve the company's operational performance and support overallbusiness sustainability through optimal procurement decisions and better stockmanagement.Keywords: Forecasting, Inventory Control, Production, Raw Material requirements,Stock